Sprawozdawczość spółki zależnej jako źródło informacji dla controllingu finansowego - Gubicz-Stachowiak, Dorota; Kwiecińska, Małgorzata (Subsidiary Reports as a Source of Information in Finance Controllership, 2006)
The article describes the controllership process in a capital group. The subsidiary should to inform about everything important for development and liquidity - production, orders, sales. Every month the balance is prepared in accordance with National Law and Generally Accepted Accounting Principles - GAAP, which contain: income statement, balance sheet, statement of cash flow, statement of owners' equity and notes. Besides of that report, the subsidiary needs to prepare a special economic analysis and control of a budget
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 104-111